MRI in uterine cancers with uncertain origin: Endometrial or cervical? Radiological point of view with review of the literature. Issue 153 (August 2022) - Gui, Benedetta; Lupinelli, Michela; Russo, Luca; Miccò, Maura; Avesani, Giacomo; Panico, Camilla; Di Paola, Valerio; Rodolfino, Elena; Autorino, Rosa; Ferrandina, Gabriella; Fanfani, Francesco; Scambia, Giovanni; et al.
Highlights: The origin of a uterine mass can be unclear after clinical examination and biopsies. Evaluation of MRI features can support the correct assessment of the origin. Cervical cancers are centered in the cervix and present parametrial invasion. Endometrial cancers are centered in the endometrial cavity and invade the myometrium. Functional imaging can add diagnostic findings. Abstract: Therapeutic options and clinical management of cervical and endometrial cancers differs significantly. When clinical and histological analysis of a uterine mass are unable to differentiate between an endocervical or endometrial origin, magnetic resonance imaging (MRI) plays a pivotal role in discriminating the anatomical origin, supporting the clinician in the treatment planning. Cervical adenocarcinomas are more likely to be centered in the cervical region and involving both cervical canal and stromal ring, with possible parametrial invasion. Endometrial adenocarcinomas usually present an elongated morphology and are centered in the endometrial cavity predominantly involving endometrium and myometrium. On contrast-enhanced sequences, cervical cancers are more frequently hypervascular compared to endometrial cancers. In cases of uncertain findings, diffusion-weighted imaging (DWI) can provide additional helpful information with significantly higher apparent coefficient diffusion (ADC) values in cervical adenocarcinomas compared to endometrial adenocarcinomas. However, even when MRI cannot precisely reveal the origin of the tumor, it provides valuable information on several prognostic factors that can help treatment planning.